Implications of public investments and external shocks on agriculture, economic growth and poverty in Papua New Guinea: An economywide analysis - Dorosh, Paul A.; Pradesha, Angga (International Food Policy Research Institute, 2022)
Policymakers in Papua New Guinea face difficult choices as to how best to promote economic growth and reduce poverty in the context of vast differences in technology and infrastructure across the country. Fluctuations in world prices of petroleum, minerals, and export crops complicate the management of the economy because of their large impacts on export earnings and government revenues, as well as household welfare. Moreover, other shocks, such as the Covid-19 pandemic that shut down major parts of the economies of PNG and the rest of the world, have far-reaching effects on various economic sectors, as well as the health and welfare of the population. This paper presents an analysis of investment options in the agricultural sector and the effects of major economic shocks to the PNG economy using an economy-wide computable general equilibrium (CGE) model that provides estimates of the economic linkages between production, household incomes, consumption, investment, and trade. The model’s base data, a Social Accounting Matrix (SAM) for 2019, and many of the parameters are derived from the national accounts, household surveys and other data for PNG. It is important to realize, however, that even though the SAM and model structure provide a framework that guarantees a consistency of many of the assumptions, there remain many uncertainties in the data. Thus, the results presented here should not be interpreted as exact estimates, but only approximations of potential effects of policies and external shocks. The plan of this paper is as follows. Chapter 2 provides an overview of agriculture and economic growth in PNG over the last two decades, highlighting the declining share of agriculture in GDP despite positive agricultural GDP growth rates and changes in the real exchange rate that have major implications for incentives in the economy. Chapter 3 then presents a summary of the economy-wide model used in the analysis. Details of the model are found in the annexes and in the references included in the paper. Design of the model simulations and model results are discussed in Chapter 4. These simulations cover various investments in agriculture and transport infrastructure, increases in world prices of petroleum and natural gas, price increases for agricultural exports and hypothetical carbon credits tied to a reduction in exports of forestry products. Chapter 5 concludes with a summary of the main findings, policy implications and suggested areas for further work.